The Ultimate Survey: Asking One Question at a Time to Get Feedback from Library Users. Issue 1 (2nd January 2020) - Camacho, Leticia; Wages, Brian; Harris, Taylor
ABSTRACT: Libraries use surveys and other instruments to gather feedback from their users. However, with competition from many other campus entities requesting input, how can survey fatigue be avoided? To gather this feedback, the Social Sciences Reference Desk utilized a short, fun and easy method. Each week for 10 weeks during the fall semester of 2017, the reference assistants wrote a survey question on a whiteboard and provided sticky notes for patrons to write their answers. The survey provided valuable information about patrons' needs and expectations. It also fostered changes that were easily implemented to improve the delivery of library services.